Sign up ×
MathOverflow is a question and answer site for professional mathematicians. It's 100% free, no registration required.

For $n$ a natural integer congruent to $7$ modulo $8$, one has seemingly always $$\sum_{k=1}^{(n-1)/2}\left(\frac{k}{n}\right)k=0$$ where $\left(\frac{k}{n}\right)$ denotes the Jacobi symbol.

First cases:

$n=7$: $1+2-3$

$n=15$: $1+2+4-7$

$n=23$: $1+2+3+4-5+6-7+8+9-10-11$

I do not see any reason for this. Did I miss something obvious?

share|cite|improve this question
See – David Speyer Feb 1 '13 at 14:50

1 Answer 1

up vote 15 down vote accepted

There are probably lots of ways to see this, but here's one: let $S_1$ be the sum above, and let $$S_2 = \sum_{k=(n+1)/2}^{n-1} k \left( \frac{k}{n} \right).$$ Then $$S_1 + S_2 = S = \sum_{k=1}^{n-1} k \left( \frac{k}{n} \right).$$ Now you can rewrite $S$ (since $x \to 2x$ is a bijection mod $n$) as $$S = \sum_{k=1}^{(n-1)/2} 2k \left( \frac{2k}{n} \right) + \sum_{k=(n+1)/2}^{n-1} (2k-n) \left( \frac{2k}{n} \right) = 2S - n \sum_{k=(n+1)/2}^{n-1} \left( \frac{k}{n} \right), $$ where we used $(2/n) = 1$. Finally, we have $$S = 2S + n \sum_{k=1}^{(n-1)/2} \left( \frac{k}{n} \right),$$ by changing $k$ to $n-k$ in the summation and using $(-1/n) = -1$. So $S = -n\sum_{k=1}^{(n-1)/2} \left( \frac{k}{n} \right)$.

On the other hand, we can switch the index in $S_2$ from $k$ to $n-k$ as well, to get $$S_2 = \sum_{k=1}^{(n-1)/2} (n-k) \left( \frac{n-k}{n}\right) = -n \sum_{k=1}^{(n-1)/2} \left( \frac{k}{n} \right) + \sum_{k=1}^{(n-1)/2} k \left( \frac{k}{n} \right) = S + S_1 = 2S_1 + S_2.$$ (We used $(-1/n) = -1$ again).

Therefore $S_1 = 0.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.